PO.6.139 Effect and safety profile of belimumab and tacrolimus (B-T) combination therapy in 33 patients with systemic lupus erythematosus: a single-center retrospective analysis. (27th September 2022) - Nakai, T; Fukui, S; Kidoguchi, G; Ikeda, Y; Kitada, A; Nomura, A; Tamaki, H; Kishimoto, M; Okada, M
Abstract : Objective: Belimumab in combination with mycophenolate mofetil has been proven to be effective for treating systemic lupus erythematosus (SLE) in several randomized controlled trials. Calcineurin inhibitors, tacrolimus, and voclosporine are also useful in controlling the activity of lupus nephritis. However, the safety and effectiveness of belimumab-calcineurin inhibitor combination therapy has not been addressed. Therefore, we conducted a single-center retrospective study to analyze the safety and efficacy profile of belimumab-tacrolimus (B-T) combination therapy in patients with SLE. Methods: Patients with SLE administered tacrolimus and belimumab during the course of treatment were included in the study, and samples collected were analyzed for the drug retention rate, SLE flare rate, infection incidence rate, and glucocorticoid-sparing effect of the B-T combination therapy. Results: In total, 33 patients with SLE were treated with B-T combination therapy at our institution. Four patients discontinued the treatment because of insufficient response/adverse events. The drug retention rate was more than 90% at week 52 and approximately 80% at day 1000. Only one patient developed serious infection. The LLDAS achievement ratio was 9.1% on the day of initiation, and improved to 63.3% at week 26 and to 64.0% at 52 weeks after initiation. SLE flares were observed in only 3 patients (9.1%) in the first 52 weeks after initiation, and in 5 patients (15.2%) throughout the study period. A glucocorticoid-reducing effect was also observed in patients treated with B-T combination therapy. Conclusion: In most patients with SLE, B-T combination therapy was well-tolerated, and showed a good efficacy profile and glucocorticoid reducing effect. Thus, B-T combination therapy can be a feasible option for patients with refractory lupus.